Moving Spaces and Places : Interdisciplinary Essays on Transformative Movements Through Space, Place, and Time. - Boonstra, Beitske (Emerald interdisciplinary connexions, 2022)
Moving Spaces and Placesis a cross-disciplinary collection about movement as a transformative experience, showing how movement changes affect and percept of spaces and place and solidifies space into meaningful places.